Poligami: Berdasarkan Konsep Keadilan dan Teori Limit Muhammad Syahrur - Faisol Muzakky; Nerisma Eka Putri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The discourse of polygamy is a topic that reaps the pros and cons among the Ulama’ and becomes a hot topic of discussion at the community level. Full attention of Islam regarding polygamy is not merely done without conditions, but Islam stipulates polygamy on the condition that is fair and there are restrictions on the number of wives. For his reason, reseaechers are interested in conducting deeper research on the concept of justice of polygamy practices which are still a topic of debate among the public based on the limit theory by Muhammad Syahrur. This research uses a critical descriptive research model using a methodological comparative study approach to analyze problems using the limit theory put forward by Muhammad Syahrur. This type of research is library research. Te source of this research is obtained from two legal materials, namely premier and secondary. This research uses isis analysis technique to find data to adjust the object to be studied by focusing on criticism. So that the results found that Syahrur argues that polygamy must be implemented when there has been a probem in society, but also must leave the practice when no problem is found. The concept of the limit theory put forward by heading the two conditions, including the first, namely that the second, third, or fourth wife is a widow who has an orphan, than the second is the fear of not being able to be fair to the orphan, as stated in Surah An-Nisa’ verse 3.